THE EMPLOYMENT OF ROLE PLAY IN LEARNING ENGLISH TOMOTIVATE THE FIRST YEAR STUDENTS OF SMP NEGERI 1KARTASURA ACADEMIC YEAR 2007-2008 - NURTIYANI, NURTIYANI (2011)
The research is carried out to find out : (1) the effectiveness of role-play in motivating students in SMP N 1 Kartasura to learn English, (2) the problems faced by teacher in applying role-play technique, and (3) the problems faced by students in SMP N 1 Kartasura in learning process by role-play technique. The method used in this research is class action research. The research was conducted from August 2007 until November 2007. The result of the study shows that students' motivation and students' activity are increasing during the use of role play technique in the learning process. It can be concluded that (1) the role play technique is effective to motivate students in learning English, (2) the problems faced by teacher in implementing role play technique are the size of class and the limited time, (3) the problems faced by students are students' personality and limited time.